Maori sovereignty: the Maori perspective - Melbourne, Hineani (Hodder Moa Beckett, 1995)
Keywords: ethnic identity; government relations; mmp electoral system; race relations; rangatiratanga; social conditions; tiriti o waitangi/treaty of waitangi; treaty claims

Te pooti Maaori: Maaori representation and electoral reform - Farrell, Michael Kevin (Occasional paper / Centre for Maaori Studies and Research, University of Waikato, no. 33, 1992)
Keywords: government; history; mmp electoral system; suffrage

Indigenous Participation in Elective Bodies: The Maori in New Zealand - O'Sullivan, Dominic; Xanthaki, Alexandra (International Journal on Minority and Group Rights, 2009)
The article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of effective indigenous participation in the political life of the state. Such state practice that implements the 2007 UN Declaration on the Rights of Indigenous Peoples firmly confirms the position of the Declaration within current international law.
Keywords: UNDRIP; elections; electorates; government; indigenous rights; mmp electoral system; political participation; te pāti māori

The 1996 General Election and the Labour vote in the Māori electorates - O'Sullivan, Dominic (He pūkenga kōrero : a journal of Māori studies, 1999)
Explores the background to Māori representation in Parliament before tracing the development of Labour's acquisition of the Māori vote up until 1...
Keywords: kāwanatanga; labour party; mmp electoral system; māori electorates; māori seats; parliament; ratana